Effectiveness of heat source/sink and Lorentz force constraints in a non-Newtonian peristaltic arterial blood hybrid nanofluid past an overlapping stenotic artery - Vedhesh Dhinakaran; Keerthi Devarajan Anuradha; J.U. Viharika; Umair Khan; Nermeen Abdullah; Samia Elattar (Case Studies in Thermal Engineering)
Recently a considerable amount of attention has been directed towards the technological advancements in the study of arterial stenosis. The deposition of adipose tissues and saturated fatty acids and the abnormal growth of flesh, narrows the arteries, leading to restricted blood flow. This causes cardiovascular diseases like atherosclerosis, atherogenesis, atheroma, etc. Considering this the present research paper develops a Casson fluid model to investigate magnetohydrodynamic peristaltic transport of the passage of blood through slightly stenosed arteries due to the influence of copper (Cu) and alumina (Al2O3) nanoparticles. The problem is formulated using appropriate mathematical models employing non-dimensional parameters and stenosis approximations. The study has its applications in the field of medicine. The outcome of this work is that it helps to handle many heart conditions. The findings of this investigation may have benefits in various academic fields, including pharmaceuticals and other industries. In addition, they are remarkably beneficial in the treatment of numerous cardiovascular diseases.